MEREDUKSI KECEMASAN MATEMATIKA SISWA SMP MELALUI IMPLEMENTASI COOPERATIVE LEARNING TIPE GROUP INVESTIGATION - Dzulfikar, Ahmad (Universitas Wiralodra, 2016)
This study was a Quasi Experiment: The Post-test Only Non- Equivalent Group Design. This study aimed to investigate the differences in students’ math anxiety was treated Cooperative Learning of the Group Investigation Type and conventional learning. The instruments used in this study were math anxiety scale and students’ daily journal. This study resulted in the finding that there was no difference of students’ math anxiety in both classes. However, judging from the students’ daily journal, students’ math anxiety of Cooperative Learning of the Group Investigation Type class showed a downward trend compared to the conventional class students tend to fluctuate. Therefore, further research is needed to investigate the effect of Cooperative Learning of the Group Investigation Type on students’ math anxiety.